Kepastian Hukum Terhadap Notaris yang Diangkat Sebagai Pejabat Negara - Safira Aulia Nisa; Bayu Dwi Anggono; Ayu Citra Santyaningtyas (CV. Syntax Corporation Indonesia, 2021)
The role of a notary is needed by the community in daily life in order to create certainty, discipline, and legal protection. In carrying out his duties and occupations, a notary must follow or obey the rules stated in the UUJN. However, there are some shortcomings found in the UUJN, one of the shortcomings is the procedures that must be carried out by a notary who is appointed as a state official. The shortcoming intended is the presence of a different understanding between the rules for dismissal for notaries who hold concurrent positions as state officials, namely Article 3 letter g juncto with Article 8 section (1) letter e and Article 17 section (1) letter d juncto with Article 17 section (2) letter c with articles that require leave for notaries who are appointed as state officials, namely Article 11 section (1) and Article 25 section (3) and Article 32 section (1) of the UUJN. Different understandings between articles in UUJN lead to concurrent positions between notary positions and state officials. In order to solve this problem, it is necessary to know the meaning of the words resign and leave according to UUJN for notaries who are appointed as state officials, besides that knowing about the provisions for notaries who are appointed as state officials whether they can regain their position as notary. And it is also necessary to reevaluate the articles in UUJN related to future regulations for notaries who are appointed as state officials. In this paper, the type of empirical juridical research is used, which is not only guided by the scientific method but also by examining the real condition in the field, especially in the provisions for notaries who are appointed as state officials. The results of the research in this paper, namely based on the meaning of the words stop and leave for a notary who is appointed as a state official according to UUJN does not make a difference, a notary who is on leave because he is appointed as a state official can return to being a notary when his term of office is over but if he does not take leave procedures and is considered to have concurrent positions, it is not necessarily possible to become a notary again even though the term of office as a state official has ended, in the future two concepts should be given, namely applying leave without a substitute notary or the dismissal of a notary from his position when he prefers to become a state official